2013
DOI: 10.3390/en6105382
|View full text |Cite
|
Sign up to set email alerts
|

A Neural-Network-Based Nonlinear Adaptive State-Observer for Pressurized Water Reactors

Abstract: Abstract:Although there have been some severe nuclear accidents such as Three Mile Island (USA), Chernobyl (Ukraine) and Fukushima (Japan), nuclear fission energy is still a source of clean energy that can substitute for fossil fuels in a centralized way and in a great amount with commercial availability and economic competitiveness. Since the pressurized water reactor (PWR) is the most widely used nuclear fission reactor, its safe, stable and efficient operation is meaningful to the current rebirth of the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…where z is given by (28) and (29), z , S,Ŝ andˆ S is defined by (10), (11), (20) and (21) respectively, activation function s is chosen as the hyperbolic tangent function given by (12), feedback gain k NP is a positive scalar which satisfies (63), both feedback gains k TP and k TD are positive scalars chosen experientially, both W and V are given positive scalars, and both W and V are given positive-definite matrices.…”
Section: Control Designmentioning
confidence: 99%
See 1 more Smart Citation
“…where z is given by (28) and (29), z , S,Ŝ andˆ S is defined by (10), (11), (20) and (21) respectively, activation function s is chosen as the hyperbolic tangent function given by (12), feedback gain k NP is a positive scalar which satisfies (63), both feedback gains k TP and k TD are positive scalars chosen experientially, both W and V are given positive scalars, and both W and V are given positive-definite matrices.…”
Section: Control Designmentioning
confidence: 99%
“…Arab-Alibeik proposed a multilayer perception (MLP) based inverse power-level control for the PWRs [10]. Dong gave an MLP-based nonlinear state-observer which provides the convergent and bounded state-observation for those PWR-like nuclear reactors [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on global warming and abnormal climate phenomena found that the energy used for electricity generation results in carbon dioxide (CO 2 ) emissions and greenhouse effects [8][9][10]. To slow down CO 2 emissions and generate cleaner electricity, previous studies have suggested the usage of clean energy to replace fossil fuels [11][12][13]. Previous studies have regarded nuclear energy or renewable energy as clean energy that can be used to generate electricity and have proposed using clean energy to replace fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
“…Neural networks (NNs) have an inherent ability to learn and approximate nonlinear systems with an arbitrary accuracy [15]. Some kinds of feedforward NNs provided suitable and improved modeling performance in PWR systems [16]- [18]. However, the main drawback of feedforward NNs is that they are essentially static and limited in representing complex systems.…”
Section: Introductionmentioning
confidence: 99%